In-situ NDT investigation to estimate degraded quality of concrete on existing structure considering time-variant uncertainties. (January 2020) - Dey, Abhijeet; Miyani, Ghanshyam; Debroy, Sudipta; Sil, Arjun
Abstract: Concrete structures may be affected due to degradation of stiffness or strength originated from severe environmental stressors or unsystematic variations in the loads and resistances of the structure beyond the baseline conditions of the existing design. Therefore, physical changes in the performing system should be considered for assessing the future reliability and safety of the structure. In this paper an improved approach for the evaluation of time-dependent structural reliability of aged structure has been presented. Experimental investigation has been carried out using two different Non-Destructive testing (NDT) methods, such as 'Rebound hammer (RH)' and Ultrasonic pulse velocity (UPV) methods to check the deterioration of the existing structure with respect to age and load processes, however, the results have been used for the evaluation of failure probability of the structure with respect to time or ages. The quality of the degraded concrete is suitably represented by a normalized index called Concrete Quality Designation (CQD). Considering non-stationarity in the process of load and time-dependent structural resistance, the assessment for time-dependent structural reliability is performed to investigate and assess the structural degradation characteristics reliably for safety evaluation of the remaining service life of structure. Highlights: The evaluation of time-dependent structural reliability of aged structure has been presented. Experimental investigation has been carried out using two different NDT methods, viz. RH method and UPV method. NDT methods have been used to check the deterioration of the structure with respect to age and load processes. Evaluation of failure probability of the structure with respect to time. The quality of the degraded concrete is suitably represented by a normalized index called Concrete Quality Designation (CQD).